Spontaneous Clearance of Hepatitis C after Liver and Renal Transplantation - CH Dale; P Burns; M McCutcheon; R Hernandez-Alejandro; PJ Marotta (Canadian Journal of Gastroenterology)
Spontaneous clearance of hepatitis C virus (HCV) is rare in immunocompromised patients, such as those who have undergone organ transplantation. It has been recognized that patients receiving liver transplantation for HCV-related disease have decreased graft and patient survival compared with those transplanted for other etiologies. There is a growing trend toward treating HCV recurrence aggressively after liver transplantation. For other organ transplant recipients with concurrent HCV, treatment is not often an option, given the high rates of graft rejection and loss secondary to interferon and its immunomodulatory effects. Although spontaneous clearance of HCV has been reported in recipients of solitary liver and renal transplants, a common factor arising in these cases has been previous exposure to interferon. To date, no reports of spontaneous clearance of HCV RNA have been reported in a multiorgan transplant recipient. A case of spontaneous clearance of HCV RNA in an immunocompromised patient, within five months of simultaneous liver and kidney retransplantation is described. Importantly, this patient had no previous exposure to interferon.